Using serum troponins to screen for cardiac involvement and assess disease activity in the idiopathic inflammatory myopathies. (12th March 2018) - Lilleker, James B; Diederichsen, Axel C P; Jacobsen, Søren; Guy, Mark; Roberts, Mark E; Sergeant, Jamie C; Cooper, Robert G; Diederichsen, Louise P; Chinoy, Hector
Abstract: Objectives: Limitations in the methods available for identifying cardiac involvement and accurately quantifying disease activity in the idiopathic inflammatory myopathies (IIMs) may contribute to poor outcomes. We investigated the utility of different serum muscle damage markers [total creatine kinase (CK), cardiac troponin T (cTnT) and cardiac troponin I (cTnI)] to address these issues. Methods: We assessed disease activity and cardiac involvement using the International Myositis Assessment and Clinical Studies Group core set measures in 123 participants with confirmed adult-onset IIM from the UK and Denmark. Total CK, cTnT and cTnI were measured. Associations were assessed using logistic regression and Spearman's ranked correlation. Results: Cardiac involvement ( n = 18) was associated with higher cTnI levels, independent of overall disease activity [adjusted odds ratio 1.03 (95% CI 1.01, 1.05); P = 0.002]. An abnormal cTnI had the highest specificity and positive predictive value for cardiac involvement (95% and 62%, respectively). In those with a normal CK but elevated cTnT or cTnI, an association with increased disease activity scores was observed. Serum cTnT correlated with the physician (ρ = 0.39) and patient-assessed (ρ = 0.28) global visual analogue scales and HAQ (ρ = 0.41) more strongly than CK or cTnI levels. cTnT was the only marker to correlate with manual muscle testing scores (ρ = −0.24). Conclusion: Serum cTnI testing may have a role in screening for cardiac involvement in IIMs. Abnormal levels of serum cTnT and cTnI are associated with increased disease activity, including in those with a normal CK.